Marayniocus martensi, a new genus and a new species of Peruvian harvestmen (Arachnida: Opiliones: Gonyleptidae) - Acosta, Luis E. (Zootaxa, 2006)
A new genus and a new species of Gonyleptidae (Pachylinae) from the Peruvian Andes, Marayniocus martensi, are described. The generic distinction is primarily based on the male genitalia, especially the ventral process of the stylus, which is fan-shaped and bears an acute ventral apophysis; such a structure has no parallel among other Andean pachylines. Exomorphological and genital differences between Marayniocus gen. n. and the Andean genera Acrographinotus, Junicus, Punagraphinotus, Palcapachylus, Tarmapachylus and Pichitus are discussed. The new species has been collected in high altitude grasslands south of the Chanchamayo basin, on the eastern Andean slopes of central Peru.